An Adaptive Pesantren Balanced Scorecard Model for Integrating Islamic Values into Educational Quality Measurement - Imamah, Istianatul; Aimah, Siti; Fakhruddin, Fathiyah Mohd (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
Previous studies have rarely examined a Balanced Scorecard (BSC) framework that holistically measures Islamic education quality while accommodating both modern accountability requirements and the spiritual authenticity of pesantren. This study aims to develop and analyze an adaptive pesantren value-based Balanced Scorecard model that integrates local religious values into a measurable performance management system for sustainable quality improvement. The study employed a qualitative case study design conducted at Darussalam Islamic Boarding School, Indonesia. Data were collected through in-depth interviews with leaders, managers, and teachers, participant observation of institutional practices, and analysis of strategic documents and performance reports. The data were analyzed through an interactive process of data reduction, display, and verification to generate an empirically grounded model. The findings reveal that the BSC integration transformed evaluation practices from reliance on the kyai’s intuition to a systematic, data-driven mechanism characterized by standardized indicators, periodic reporting, and evidence-based decision-making. Internal processes became more professional through the establishment of a Multimedia Team responsible for measurable digital documentation and outreach. At the same time, traditional learning activities such as ngaji kitab kuning and adab education were not replaced but strengthened through structured monitoring. These dynamics produced a hybrid quality model that combines religious authenticity with managerial accountability. The novelty of this study lies in the operationalization of pesantren values into concrete Key Performance Indicators across the four BSC perspectives, moving beyond purely conceptual approaches to spirituality. The study contributes theoretically by extending performance management literature within faith-based education and practically by offering a replicable framework for religious institutions seeking sustainable and measurable quality improvement.